Training of Highly Qualified Scientific Personnel in Pedagogical Sciences: Retrospective Analysis (2011–2020) - L. V. Shchegoleva; S. I. Pakhomov; V. A. Gurtov (Высшее образование в России)
Pedagogical sciences occupy a significant place in the system of training and certification of highly qualified scientific personnel. During the period from 2011 to 2020, about 10 thousand dissertations were defended in pedagogical sciences, which is 6.5% of the total number of defenses within the entire certification system. The subject of dissertations should correspond to the challenges of modern society and be aimed at the topical problems of youth education. The purpose of the study is a general assessment of the system of training and certification of candidates and doctors of pedagogical sciences, the development and testing of a method for identifying the mainstream in the subject of dissertation research and quantifying the implementation of priority pedagogical research directions in dissertation works for a ten-year retrospective period.The results of the analysis revealed a reduction in the number of dissertation defenses in pedagogical sciences, which is in line with the general trend of reducing defenses, aging of dissertation councils members, a small number of young doctors of sciences. Thematic analysis of dissertations has shown that research meets the challenges of modern society, while there is a slight thematic delay associated with the time duration of the procedure for preparing and defending a dissertation. The largest number of dissertations was devoted to various issues of higher education in comparison with the other levels of education. Among the academic disciplines, foreign language, mathematics, Russian language and computer science have gained the greatest popularity in the subject of dissertation research. The thematic mainstream includes the formation of professional and communication competencies.